2001
DOI: 10.1292/jvms.63.1327
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Immunological Response after Experimentally Ozonated Autohemoadministration in Calves.

Abstract: ABSTRACT. Changes in subsets of peripheral blood mononuclear cells and lymphocyte blastogenesis reaction were observed after ozonated autohemoadministration (OAHA) in calves. Ten healthy calves were used in this study. After OAHA, CD8 + cells, CD14 + cells and WC1 + cells increased (p<0.05). The level of lymphocyte blastogenesis stimulated by PHA decreased after OAHA. A significant increase in serum IL-6 activity was observed in OAHA calves. These results suggested that OAHA induced immunological changes in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Previously, we reported increased B cells after OAHA in healthy calves following increased serum IL-6 activity [19]. Larini and Bocci [9] reported that exposure to ozone induced marked IL-4 production in isolated peripheral blood mononuclear cells, and discussed a significant relationship between cytokine production and ozone concentrations.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, we reported increased B cells after OAHA in healthy calves following increased serum IL-6 activity [19]. Larini and Bocci [9] reported that exposure to ozone induced marked IL-4 production in isolated peripheral blood mononuclear cells, and discussed a significant relationship between cytokine production and ozone concentrations.…”
mentioning
confidence: 90%
“…Although ozone therapy has been reported to be effective in humans, the immune response to ozonated autohemotherapy has not been clarified in vivo, and the effect of ozonated autohemotherapy on peripheral leukocyte populations remains largely unknown in humans. Previously, we reported that ozonated autohemoadministration (OAHA) induced an increase of peripheral T cell and serum IL-6 activity in healthy calves [19]. But there have been no studies of peripheral lymphocyte populations after OAHA in cows with inflammatory diseases such as mastitis or arthritis.…”
mentioning
confidence: 99%
“…1995; Guennadi et al. 2008) properties that support its current application in medicine and dentistry (Terasaki et al. 2001; Guennadi et al.…”
Section: Introductionmentioning
confidence: 99%
“…A novel approach using ozone (O 3 ) containing products may be considered in the treatment of retained placenta as well, because of its reported bactericidal (Bocci 1996;Silva et al 2009), immune-stimulating (Buckley et al 1975;Jakab et al 1995;Zimran et al 2000;Guennadi et al 2008) and anti-inflammatory (Jakab et al 1995;Guennadi et al 2008) properties that support its current application in medicine and dentistry (Terasaki et al 2001;Guennadi et al 2008;Silva et al This research was carried out in the central part of Croatia (Moslavina region). Presented manuscript has been read and approved by all included authors.…”
Section: Introductionmentioning
confidence: 99%
“…1975; Mehlman and Borek 1987; Ogata and Nagahata 2000; Zimran et al. 2000; Terasaki et al. 2001; Ohtsuka et al.…”
Section: Introductionmentioning
confidence: 99%